Strategi Televisi Dalam Mempertahankan Eksistensi Di Era Digital Inspira TV - Sari, Ulfi Nopita; Anugrah, Dadan; Tresnawaty, Betty (Jurusan Ilmu Komunikasi, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Djati Bandung, 2020)
This study aims to determine and analyze television media strategies in maintaining existence in the digital era (descriptive study on Inspira TV). This research uses the concept of STP (Segmenting, Targeting, Positioning) from Kotler. The concept of STP in television media is used to determine three things, namely market segment (segmenting), target audience (targeting), and desired position in the market (positioning). Through this STP concept, will provide a description of Inspira TV's strategy in maintaining existence in the digital era. The research method to be carried out by researchers is a descriptive method with a qualitative approach. The results of the study concluded Inspira TV is segmenting demographics for young people and viewers with families, is developing geographical segmentation. The target audience is young people and families, with a variety of programs on social media. Inspira TV Bandung positions itself as a medium of information and inspiration, and brands itself as Edutainment.